Iraq - Owings, Lisa. (Minneapolis, MN : Bellwether Media, 2011)
"Developed by literacy experts for students in grades three through seven, this book introduces young readers to the geography and culture of Iraq"--Provided by publisher.
Where is Iraq? -- The land -- The marshes -- Wildlife -- The people -- Daily life -- Going to school -- Working -- Playing -- Food -- Holidays -- Iraqi art -- Fast facts -- Glossary.
Includes bibliographical references (p. 31) and index.
Keywords: Iraq -- Juvenile literature